Dilemmas of Remote Meetings of Councils of Local Government Units in the Post-Pandemic Perspective - Wilk, Bartosz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Remote meetings of local government units were introduced in 2020 due to the COVID-19 pandemic. The possibility of remote meetings served both to protect public health and to ensure that the decision-making body could act efficiently. The purpose of this text is to identify the regulatory dilemmas that the legislator would have to face if the possibility of remote meetings were to be regulated in the legal system in the post-pandemic perspective. Selected legal and practical problems related to the functioning of remote meetings in 2020–2022 were analysed. Both the introduction of the possibility of adopting resolutions by correspondence by decision-making bodies and the legitimacy of adopting such a solution in the post-pandemic perspective were critically assessed.